Justification for use of energetic separators for gas distributive stations - Yurkevych, Yuriy; Savchenko, Olena (Видавництво Львівської політехніки, 2013)
This paper shows the efficiency of energetic separators for gas distributive stations and ustified the necessity of replacing existing types of heaters by gas energetic separators. Показано ефективність роботи енергетичних роздільників на газорозподільних станціях та обґрунтовано необхідність заміни існуючих типів підігрівників газу на енергетичні роздільники.
Keywords: gas distributive station; natural gas; gas preheater; energetic separator; газорозподільна станція; природний газ; підігрівники газу; енергетичний роздільник